Effects of rhubarb peony decoction combined with antibiotics in treating pediatric periappendiceal abscess - Lin, Zhixiong; Zeng, Huiping; Cai, Shujie; Chen, Fei; Wang, Xiang; Wu, Dianming; Liu, Mingkun; Fang, Yifan (Frontiers in Pediatrics, 2023)
Background/purpose Rhubarb peony decoction (RPD) is a formula of traditional Chinese medicine that has been widely used to treat intra-abdominal inflammatory diseases. To investigate the therapeutic efficacy of RPD in pediatric periappendiceal abscess, patients who received intravenous antibiotics alone were compared with those treated with intravenous antibiotics combined with RPD. Methods A retrospective review of children with periappendiceal abscess who received conservative treatment in our hospital between January 2013 and April 2022 was performed. The patients were divided into an intravenous antibiotic group (the control group) and an intravenous antibiotic combined with RPD group (the intervention group). Interval appendectomy (IA) was generally performed 10–12 weeks after conservative treatment. The primary outcome was the cure rate of conservative treatment, while the secondary outcomes included the recurrence rate, days of total intravenous antibiotic use, length of hospital stay (LOS), postoperative complications, and liver injury caused by RPD. Results A total of 142 patients (77 girls and 65 boys) were included, 52 in the control group and 90 in the intervention group. The two groups were similar in demographic data and clinical characteristics (P > 0.05). The mean total course of RPD in the intervention group was 11.82 days. The intervention group had a significantly higher cure rate than the control group (93.33% vs. 80.77%, P = 0.029), and the length of total intravenous antibiotic use (P = 0.150), LOS (P = 0.077), recurrence rate (9.52% vs. 4.76%, P = 0.439), as well as the operation time (P = 0.101), LOS (P = 0.572), and postoperative complications (P = 0.549) were not significantly different between the two groups when the patients received IA. No patient had a liver injury caused by RPD during the treatment. Conclusion Intravenous antibiotics combined with RPD demonstrated high effectiveness and safety for treating pediatric periappendiceal abscess.